CP-048 Multidisciplinary management as a resource for metabolic diseases: cooperation between clinicians and pharmacists in an Italian centre for rare diseases. (24th February 2014) - De Meo, MS; Pompilio, A; Ciuccarelli, F; Garzone, AMF; Andresciani, E; Mannucci, A; Ficcadenti, A; Marravalle, D; Moretti, V
Abstract : Background: There are almost 8, 000 rare diseases (RD) (80% are genetically based) and 50% of them affect children. They are often highly complex metabolic diseases (MD): factors include heterogeneity (age of occurrence, aetiopathogenesis and symptomatology), low numbers affected, late diagnosis, lack of curative treatments and multisystem involvement. Decree 279/2001 of Italian Minister of Health instituted the 'Rare Disease National Web' and assigns to the Regions the task of finding hospitals and organisations to supply health services. Since 2002 our hospital 'G. Salesi' has been the reference centre for Marche Region. Purpose: To strengthen cooperation between doctors, pharmacists and health workers, which was spontaneously born of individual needs and emergencies. This is needed to improve the level of treatment, respond to therapeutic/welfare necessities, and treat patients' extremely complex emergencies. Materials and methods: We checked medical records: patients with MD who enter our centre (for diagnosis, treatment and follow-up) and their prescriptions (basic treatment/emergency support). Hospital and regional doctors and pharmacists met in order to lay out shared protocols. Results: Our Centre follows 850 RD patients; 27 (13 males and 14 females) with MD: Fabry's (4), Sandhoff's (2), Gaucher's (1), mucopolysaccharidosis (6), organic acidemia (6), glycogenosis (3), leucinosis (1), Niemann-Pick type C (3) and pyruvate dehydrogenase deficiency (1). 59% are children (10 patients <10 years old). 30% need a particular diet, 18% need galenical preparations. 5 Patients have enzyme treatment in day hospital: 2 laronidase, 2 agalsidase alfa, 1 idursulfase. 26% of diagnoses comes from other centres. We wrote up a protocol to manage all the dietetic and therapeutic emergencies and sent it to all operators, especially for emergencies for metabolic acidosis, hyperammonaemia, and methylmalonic aciduria. Conclusions: The 'doctor-pharmacist' team was born to improve the quality of life of MD patients. The pharmacist's role consists of: responding to lack of resources/drugs (i.e. galenical preparations suitable for young children), helping doctors in therapeutic decisions, supporting patients and families with their healthcare needs. No conflict of interest.